Licenciatura en educación básica primaria 1983 – 1999: Recorrido histórico - Pineda de Cuadros, Nubia Elena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Pedagogical and Technological University of Colombia since 1982 was linked to the academic processes proposed at the national level in the mo- dality of distance education, in support of the population that for geogra- phical and economic reasons could not access the university education in person, favoring in this first opportunity, a group of teachers who achieved the goal of being graduates in primary basic education whose benefits were appreciated by their students in the most remote areas of the capital of the department, in this document their genesis, development and culmination are described of the program that started and strengthened in this university the modality of distance education, in favor of regional development with social responsibility in favor of students who are enrolled in the different programs offered by the Faculty of Distance Studies currently.